2014
DOI: 10.3389/fpls.2014.00454
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide patterns of segregation and linkage disequilibrium: the construction of a linkage genetic map of the poplar rust fungus Melampsora larici-populina

Abstract: The poplar rust fungus Melampsora larici-populina causes significant yield reduction and severe economic losses in commercial poplar plantations. After several decades of breeding for qualitative resistance and subsequent breakdown of the released resistance genes, breeders now focus on quantitative resistance, perceived to be more durable. But quantitative resistance also can be challenged by an increase of aggressiveness in the pathogen. Thus, it is of primary importance to better understand the genetic arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Another application is assessing the quality of an assembly ( e.g. , Pernaci et al 2014 ) or ordering scaffolds, such as in the Locus Ordering by Dis-Equilibrium procedure ( Khatkar et al 2010 ). This application of LD is perhaps less well known but is particularly useful for sequencing data, since assemblies are often fragmented or not existent, and has already been used in a study by Tennessen et al (2017) .…”
Section: Discussionmentioning
confidence: 99%
“…Another application is assessing the quality of an assembly ( e.g. , Pernaci et al 2014 ) or ordering scaffolds, such as in the Locus Ordering by Dis-Equilibrium procedure ( Khatkar et al 2010 ). This application of LD is perhaps less well known but is particularly useful for sequencing data, since assemblies are often fragmented or not existent, and has already been used in a study by Tennessen et al (2017) .…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data suggest that variability in the M. lini genome can be achieved through a high overall recombination rate, consistent with reports of high genetic diversity in natural, sexually reproducing M. lini populations [ 99 ], and an ability of the asexual stage to withstand small- and large-scale chromosomal duplications and deletions, which can both impact upon the virulence phenotype. Several mapping families have been produced for other rust fungi, including the wheat stem rust, poplar rust and pine fusiform rust fungi [ 70 , 100 , 101 ]. Approaches like those described here may facilitate genome analysis and avirulence gene cloning in these rust fungi and other species.…”
Section: Discussionmentioning
confidence: 99%
“…A genome‐wide search for single nucleotide polymorphisms or insertion/deletion in rust fungal isolates has enabled the detection of avirulence candidates among secreted protein genes (Cantu et al ., ; Bruce et al ., ; Persoons et al ., ; Upadhyaya et al ., ; Bueno‐Sancho et al ., ; Cuomo et al ., ; Wu et al ., ). Sequencing large volumes of isolates is now possible for relatively low cost, and high‐density genetic maps can be constructed through the resequencing of progenies or by restriction site detection sequencing (RAD‐seq) in rust fungi (Pernaci et al ., ; Anderson et al ., ; Yuan et al ., ). Two recent studies demonstrated the degree to which genomics has impacted the field by combining genomics and resequencing approaches to identify AvrSr35 and AvrSr50 , two P. graminis f. sp.…”
Section: Rusts In the Genomics Era: The Ever‐expanding List Of Candidmentioning
confidence: 98%